Fathers and Perceptions of God Play an Important Role in Psychological Adjustment Among Emerging Adults in Guatemala and the United States. Issue 5 (3rd September 2018) - Ashdown, Brien K.; Faherty, Amanda N.; Brown, Carrie M.; Hanno, Olivia; Belden, Alexandra; Weeks, Peter B.
Abstract: Interpersonal acceptance-rejection theory posits that people require parental acceptance in childhood to develop healthy psychological adjustment. People's beliefs about and their relationship with deity also influences their psychological adjustment. The purpose of the present study was to investigate how both perceived parental acceptance and a relationship with deity are related to psychological adjustment for emerging adults in Guatemala and the United States. Participants ( N = 189) from Guatemala and the United States completed measures of perceived parental acceptance-rejection, images of God, attachment to God, and psychological adjustment. Results indicate that perceived paternal acceptance-rejection was only a significant predictor of psychological adjustment in U.S. participants, and not in Guatemalan participants. In both samples, images of God did not predict psychological adjustment. However, an anxious attachment with God predicted psychological maladjustment for both groups. The findings suggest that two important factors to be considered by researchers, educators, and mental health professionals are adults' perceptions of their father's level of acceptance-rejection and the amount of anxiety they experience in their relationship with God.